How to Review a Surgical Scientific Paper: A Guide for Critical Appraisal. Issue 1 (19th March 2021) - Greco, Stephanie H.; Davis, Catherine H.; Hicks, Caitlin W.; Kaye, Alison E.; Maxwell, Jessica E.; Salles, Arghavan; Henry, Marion C.W.
Abstract : It is important for surgeons to participate in the peer-review process of scientific literature. As the number of published manuscripts continues to increase, there is a great need for volunteerism in this arena. However, there is little formal or informal training, which can help surgeons provide unbiased and meaningful reviews. Therefore, it is critical to provide more resources and guidelines to aid surgeons during the review process. The purpose of this paper is to provide a structured guide for a quality review of a surgical paper. This review represents the work of the Association of Women Surgeons Publications Committee. Abstract : Mini abstract: This paper provides a structured guide for the peer review of a surgical paper.